Kinect Depth Sensor Evaluation for Computer Vision Applications - Andersen, M.R.; Jensen, T.; Lisouski, P.; Mortensen, A.K.; Hansen, M.K.; Gregersen, Torben; Ahrendt, Peter (Technical Report Electronics and Computer Engineering, 2012)
This technical report describes our evaluation of the Kinect depth sensor by Microsoft for Computer Vision applications. The depth sensor is able to return images like an ordinary camera, but instead of color, each pixel value represents the distance to the point. As such, the sensor can be seen as a range- or 3D-camera. We have used the sensor in several different computer vision projects and this document collects our experiences with the sensor. We are only focusing on the depth sensing capabilities of the sensor since this is the real novelty of the product in relation to computer vision. The basic technique of the depth sensor is to emit an infrared light pattern (with an IR laser diode) and calculate depth from the reflection of the light at different positions (using a traditional IR sensitive camera). In this report, we perform an extensive evaluation of the depth sensor and investigate issues such as 3D resolution and precision, structural noise, multi-cam setups and transient response of the sensor. The purpose is to give the reader a well-founded background to choose whether or not the Kinect sensor is applicable to a specific problem.